THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT IN THE RELATIONSHIP BETWEEN WORK-LIFE BALANCE, JOB SATISFACTION, AND EMPLOYEE PERFORMANCE: EVIDENCE FROM AMANDA KALIMANTAN BROWNIES - Siti Rabiah; Saida Zainurossalamia; Wirasmi Wardhani (RADJA PUBLIKA, 2026)
This study examines the effect of work-life balance and job satisfaction on employee performance, with employee engagement acting as a mediating variable. The research was conducted in the context of employees at Amanda Brownies in East Kalimantan, representing the food and beverage industry with operational work characteristics and direct customer interaction. A quantitative approach with an explanatory research design is employed to analyze causal relationships among variables. Data are collected through questionnaires distributed to 138 employees using a saturated sampling technique. The data are analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect effects within the proposed model. The findings reveal that work-life balance and job satisfaction have a positive and significant effect on employee engagement. Furthermore, employee engagement significantly influences employee performance. The results also indicate that employee engagement plays a mediating role in the relationship between work-life balance, job satisfaction, and employee performance. These findings suggest that employee performance is not solely influenced by individual factors but is shaped by an integrated mechanism involving psychological and organizational aspects. The study provides practical implications for management in designing strategies that enhance employee well-being and engagement to improve organizational performance.